Psychologizing indexes of societal progress: Accounting for cultural diversity in preferred developmental pathways - Kuba, K. (2020)
Since the Second World War, the dominating paradigm of societal development has focused on economic growth. While economic growth has improved the quality of human life in a variety of ways, we posit that the identification of economic growth as the primary societal goal is culture-blind because preferences for developmental pathways likely vary between societies. We argue that the cultural diversity of developmental goals and the pathways leading to these goals could be reflected in a culturally sensitive approach to assessing societal development. For the vast majority of post-materialistic societies, it is an urgent necessity to prepare culturally sensitive compasses on how to develop next, and to start conceptualizing growth in a more nuanced and culturally responsive way. Furthermore, we propose that cultural sensitivity in measuring societal growth could also be applied to existing development indicators (e.g. the Human Development Index). We call for cultural researchers, in cooperation with development economists and other social scientists, to prepare a new cultural map of developmental goals, and to create and adapt development indexes that are more culturally sensitive. This innovation could ultimately help social planners understand the diverse pathways of development and assess the degree to which societies are progressing in a self-determined and indigenously valued manner.